Probing into the evolution of a polymorphic semiconductor at nanoscale / Alireza Yaghoubi Taemeh - Alireza , Yaghoubi Taemeh (2018)
Graphene is considered to be the most likely candidate for the post-silicon era however the problem with its zero band gap is challenging to overcome. A close relative of silicon, silicon carbide is expected to have a stable 2D polymorph which happens to be a wide-gap semiconductor. Unfortunately, the so-called silagraphene has proven to be elusive. To date, neither theoretical, nor experimental studies have been conclusive. In this thesis, we employ computational methods to determine the stable arrangements of silagraphene, and establish their accurate band structure. We also experimentally validate our models by preparing and characterizing a number of graphitic features. Silagraphene exhibits a wide spectrum of optoelectronic properties (360-690 nm) as well as an unusual band structure with highly anisotropic transport properties, which originates from its non-dispersive band near its K-point. This feature makes direct-indirect gap crossover extremely sensitive to ambient conditions, making silagraphene suitable for a range of sensors. We also demonstrate that a particular arrangement of atoms that represent 9R-SiC occurs when the metastable AA’ silagraphene is relaxed. This structure has a very similar microscopic and crystallographic signature to that of 3C-SiC and 15R-SiC, respectively, which might explain why it has evaded detection until now. Its vibrational footprint on the other hand is quite distinct thanks to its fewer active phonon modes. Surprisingly, the indirect band gap of this polytype is slightly wider than that of 2H-SiC, despite its lower hexagonality, and is equivalent to that of GaN. Due to its unique conduction band structure, 9R-SiC may also exhibit improved electron transport properties as compared to other SiC polytypes; and therefore could be suitable for high-frequency and high-voltage applications.